ANNE WITH AN E, REPRESENTING EQUALITY IN MARRIAGE IN THE 19th CENTURY: JOHN FISKE’S SEMIOTIC ANALYSIS - Dhea Pramesti Regita Cahyani; Dewi Candraningrum (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the representation of Anne's character confronts women'sstereotypical roles during the 19th Century by being a feminist in the center of a patriarchalsociety, fighting for equality, body autonomy, and the fundamental rights of women. The research data is from Netflix original series Anne with an E premiered seven years ago. This series based on a classic children novel set in the late 19th Century that recounts Anne Shirley's adventures. This paper focus on the third one since it is the onemore relevant to the topic and theory that will be discussed. The researcher used qualitative research method with a semiotic analysis to analayze the research object. The data analysis technique is based from “The Codes of Television” semiotics theory by John Fiske. The approach used to investigate are; the level of reality, the level of representation, and the level of ideology. Based on the data, the researcher has found in this Century and Canada, women didn’t have a voice, but Anne become that voice that many tried to silence. She fought grateefully for women’s rights, and she applied it to her life. A patriarchal society was confronted not just by Anne but by a complete change of thought. Anne’s character is a true feminist icon who fought for women’s rights and works as an example for the women of nowadays.